The effectiveness of biological agents in the composting of fallen leaves - Решетніков, М. В.; Матвєєва, О. Л. (Problems of Environmental Biotechnology, 2019)
The article is devoted to the evaluation of the effectiveness of industrial biologics for composting, bacterial associations, micromycetes.